2023
DOI: 10.1002/smll.202301589
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Engineered Mesoporous Undoped Carbon Nanoribbons for Benchmark Oxygen Reduction Reaction

Abstract: For large‐scale fuel cell applications, it is significant to replace expensive Pt‐based oxygen reduction reaction (ORR) electrocatalysts with nonprecious metal‐ or metal‐free carbon‐based catalysts with high activity. However, it is still challenging to deeply understand the role of intrinsic defects and the origin of ORR activity in pure nanocarbon. Therefore, a novel self‐assembly and a pyrolysis strategy to fabricate defect‐rich mesoporous carbon nanoribbons are presented. Due to the effective regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…38–40 On the other hand, the I D / I G ratio, representing the D and G band intensity ratio, emerges as a pivotal indicator elucidating the extent of defects in the material, with a higher I D / I G value suggesting a dominating presence of topological defects. 41 As depicted in Fig. 1d, the I D / I G ratio exhibited a significant increase from the monometallic Fe-NC@900 ( I D / I G = 0.77) to the bimetallic materials, suggesting that the incorporated Co induces defect formation.…”
Section: Resultsmentioning
confidence: 81%
“…38–40 On the other hand, the I D / I G ratio, representing the D and G band intensity ratio, emerges as a pivotal indicator elucidating the extent of defects in the material, with a higher I D / I G value suggesting a dominating presence of topological defects. 41 As depicted in Fig. 1d, the I D / I G ratio exhibited a significant increase from the monometallic Fe-NC@900 ( I D / I G = 0.77) to the bimetallic materials, suggesting that the incorporated Co induces defect formation.…”
Section: Resultsmentioning
confidence: 81%
“…104–108 It has been reported that lithium–sulfur button cells with metal phosphides have good electrochemical properties under different rates and have good cycle stability in soft package batteries. 109–111 The clearly delineated design principles and comprehensive exploration of catalytic mechanisms related to phosphides have offered significant insights for constructing excellent efficiency and long-lasting Li–S batteries. However, numerous areas remain that require persistent investigations into phosphide merchandisers.…”
Section: Discussionmentioning
confidence: 99%
“…Although platinum-based catalysts dominate ORR research, their high cost, limited availability, and vulnerability to methanol poisoning necessitate the exploration of alternative options. 116 Fe-based catalysts, especially those with Fe-N x active sites (SACs), are showing great potential as alternative electrocatalysts. Nevertheless, limitations of Fe-N x single-atom sites have prompted innovative strategies to enhance ORR efficiency.…”
Section: Orr Activity and Optimization Strategies Of Particle@fe-n-cmentioning
confidence: 99%